اسلامی اور عصری قوانین میں سائبر کرائمز کے چیلنجز: ایک تجزیاتی مطالعہ: Challenges of Cybercrimes in Islamic and Contemporary Legal Systems: An Analytical Review - Asrar Ahmed, Dr. Fazail; Hussain Chuhan, Munawar (Al-Amīr Research Journal for Islamic Studies, 2025)
The rising issue of cybercrimes has presented new challenges to legal systems worldwide and has become a serious problem in contemporary times. Modern laws have implemented various measures to curb cybercrimes; however, due to a lack of international cooperation, legal inconsistencies, and the rapid advancement of technology, these laws often prove inadequate. This study analyzes the challenges of these crimes in the context of Islamic and contemporary laws and emphasizes the need for harmony between them to provide a comprehensive and effective solution to cybercrime issues. By promoting ijtihad (independent reasoning), public awareness, and international cooperation, these crimes can be prevented. The study concludes that integrating the ethical foundations of Islamic principles with the practical techniques of contemporary laws can create a sustainable and just system capable of addressing cybercrimes effectively. Keywords: Cybercrimes, Islamic Laws, Contemporary Laws, Legal Challenges , International Cooperation, Legal Systems, Ethical Foundations, Ethical Foundations , Technology and Law.